The effect of wok family conflict on Employee performance: does income Matter of influence? - Kengatharan, N. (University of Jaffna, 2017)
Seminal research studies in the sphere of work family conflict lend credence to the notion that work family conflict is a deleterious factor hampering employee performance at work. Consequently, this study close looks at the moderating role of income in buffering the negative relationship between work family conflict and employee performance. Using a random sampling technique, a total of 124 employees working in apparel industry located in Trincomalee district were selected. Data were garnered using self-administrated questionnaire. The results revealed that the level of income moderated the relationship between work family conflict and employee performance. The results show that the negative relationship between work family conflict and performance is stronger with employees at low levels of income than those at high levels of income. This study makes a theoretical contribution to the frontiers of work family conflict and proffers practical implications that would serve as a springboard for future research studies.
Keywords: Apparel industry; Employee performance; In come; Work family conflict